Lead-acid battery

JP7651905B2Active Publication Date: 2025-03-27GS YUASA CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021055860
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-03-27
Estimated Expiration
2041-03-29

Smart Images

  • Figure 0007651905000002
    Figure 0007651905000002
  • Figure 0007651905000003
    Figure 0007651905000003
  • Figure 0007651905000004
    Figure 0007651905000004
Patent Text Reader

Abstract

To provide a lead acid battery having good cycle characteristic.SOLUTION: A lead acid battery hereof comprises a plurality of positive electrode plates 31 and a plurality of negative electrode plates 32 which are arranged to alternate, separators 40, and an electrolyte solution. The separators include a first separator 41 including a nonwoven fabric configured of organic fibers, and a second separator 42 including a glass fiber mat, which are arranged so that the nonwoven fabric and the glass fiber mat are laminated between one positive electrode plate and the negative electrode plate adjacent to the positive electrode plate. On condition that a proportion of a volume of pores Pf in a range of 0.01-15.0 μm in diameter to a total volume of pores Pf of the nonwoven fabric when measuring all the pores Pf by a mercury penetration method is Vf(%), and a proportion of a volume of pores Pg in a range of 0.01-15.0 μm in diameter to a total volume of pores Pg of the glass fiber mat when measuring all the pores Pg by the mercury penetration method is Vg(%), the ratio Vf / Vg falls in a range of 0.5-1.2.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lead-acid battery. [Background technology]

[0002] Lead-acid batteries are used in various applications, such as in-vehicle and industrial applications. A lead-acid battery includes a positive electrode plate, a negative electrode plate, and a separator disposed between them. Various performances are required for the separator of a lead-acid battery. For this reason, lead-acid batteries using various separators have been proposed in the past.

[0003] Patent Document 1 (JP Patent Publication No. 10-40896) discloses "a sealed lead-acid battery characterized in that a separator is made of a mat of fine glass fibers and a synthetic fiber nonwoven fabric that has been treated to be hydrophilic."

[0004] Patent Document 2 (WO 2013 / 046498) discloses "a separator structure for a battery comprising a laminate of an acrylonitrile-based fiber nonwoven fabric separator and a glass fiber mat separator, wherein the acrylonitrile-based fiber nonwoven fabric separator contains at least acrylonitrile-based fine fibers having a diameter of 0.5 μm to 2.0 μm." [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 10-40896 [Patent Document 2] International Publication No. 2013 / 046498 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the conventional lead-acid batteries often have insufficient cycle characteristics, and in particular, when they undergo charge-discharge cycles involving high-rate discharge, the cycle life of the batteries is significantly reduced. [Means for solving the problem]

[0007] One aspect of the present invention relates to a lead-acid battery, which includes a plurality of positive and negative plates arranged alternately, a separator, and an electrolyte, the separator including a first separator including a nonwoven fabric made of organic fibers and a second separator including a glass fiber mat, the nonwoven fabric and the glass fiber mat are arranged to be laminated between the positive plate and the negative plate adjacent to the positive plate, and mercury is injected into pores Pf of the nonwoven fabric. When the pores Pg of the glass fiber mat are measured by a mercury intrusion method, the ratio of the volume of the pores Pg having a diameter in the range of 0.01 μm to 15.0 μm to the volume of all the pores Pf is Vf (%), and when the pores Pg of the glass fiber mat are measured by a mercury intrusion method, the ratio of the volume of the pores Pg having a diameter in the range of 0.01 μm to 15.0 μm to the volume of all the pores Pg is Vg (%), and the ratio Vf / Vg is in the range of 0.5 to 1.2. Effect of the Invention

[0008] According to the present invention, a lead-acid battery having good predetermined cycle characteristics can be obtained. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view showing a schematic configuration of a lead-acid battery according to one embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view showing a schematic configuration of an example of an electrode plate group used in the lead-acid battery shown in FIG. 1. [Diagram 3] 1. FIG. 3 is a cross-sectional view showing a schematic configuration of another example of an electrode plate group used in the lead-acid battery shown in FIG. [Figure 4] 1 is a graph showing characteristics of a lead-acid battery manufactured in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In the following, the embodiment of the present invention will be described with examples, but the present invention is not limited to the examples described below. In the following description, specific numerical values ​​and materials may be exemplified, but other numerical values ​​and materials may be applied as long as the effects of the present invention can be obtained. In this specification, the range described as "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "A or more and B or less."

[0011] (lead acid battery) The lead-acid battery according to this embodiment includes a plurality of positive and negative plates arranged alternately, a separator, and an electrolyte. The separator includes a first separator including a nonwoven fabric made of organic fibers, and a second separator including a glass fiber mat. The nonwoven fabric may be referred to as "nonwoven fabric (F)" below. The nonwoven fabric (F) and the glass fiber mat are arranged so as to be laminated between the positive plate and the negative plate adjacent to the positive plate. When the pores Pf of the nonwoven fabric (F) are measured by mercury intrusion porosimetry, the ratio of the volume of the pores Pf having a diameter in the range of 0.01 μm to 15.0 μm to the volume of all the pores Pf is Vf (%). When the pores Pg of the glass fiber mat are measured by mercury intrusion porosimetry, the ratio of the volume of pores Pg having diameters in the range of 0.01 μm to 15.0 μm to the volume of all pores Pg is Vg (%). The ratio Vf / Vg is in the range of 0.5 to 1.2.

[0012] The "volume of all pores" is the volume measured by mercury intrusion porosimetry and corresponds to the sum of the individual volumes of all pores. The "volume of pores with diameters in the range of 0.01 μm to 15.0 μm" is the volume measured by mercury intrusion porosimetry and corresponds to the sum of the individual volumes of pores determined to have diameters in the range of 0.01 μm to 15.0 μm.

[0013] Nonwoven fabrics and glass fiber mats are formed by intertwining fine fibers. Therefore, nonwoven fabrics and glass fiber mats have many tiny voids. Such tiny voids can be considered as pores. In other words, nonwoven fabrics and glass fiber mats have a porous structure containing many pores of different sizes. By performing a pore distribution analysis on such nonwoven fabrics and glass fiber mats, information on the distribution of pore diameters can be obtained.

[0014] The glass fiber mat is a mat made of glass fibers. The glass fiber mat may be called an absorbent glass mat (AGM). Therefore, in this specification, the glass fiber mat can be read as an absorbent glass mat.

[0015] The separator is required to prevent short circuits and retain the electrolyte. The glass fiber mat has a high porosity and a high electrolyte retention capacity. However, the glass fiber mat alone is insufficient to prevent short circuits. Therefore, it has been proposed to use a combination of the glass fiber mat and a synthetic fiber nonwoven fabric.

[0016] In the lead-acid batteries described in Patent Document 1 and Patent Document 2, a synthetic fiber nonwoven fabric and a glass fiber mat are used as separators. Comparing the synthetic fiber nonwoven fabric and the glass fiber mat, the glass fiber mat generally has a higher affinity with the electrolyte. Therefore, when the synthetic fiber nonwoven fabric and the glass fiber mat are laminated and used, a large amount of electrolyte is held in the glass fiber mat, while the amount of electrolyte held in the synthetic fiber nonwoven fabric tends to be small. Such an electrolyte imbalance causes various deteriorations in characteristics, such as an increase in the internal resistance of the lead-acid battery and a decrease in cycle life. In order to suppress the electrolyte imbalance, in the lead-acid batteries described in Patent Documents 1 and 2, an acrylonitrile fiber nonwoven fabric or a hydrophilically treated synthetic fiber nonwoven fabric is used as the synthetic fiber nonwoven fabric having a high affinity with the electrolyte.

[0017] The idea disclosed in Patent Documents 1 and 2 is to improve the hydrophilicity of a synthetic fiber nonwoven fabric by changing the material of the nonwoven fabric. However, such a method may not fully meet the current requirements for lead-acid batteries. For example, in a method of improving the hydrophilicity of a synthetic fiber nonwoven fabric by changing the material of the nonwoven fabric, the expected effect may not be obtained if the surface characteristics of the nonwoven fabric change due to the use of the lead-acid battery. In such a situation, as a result of investigation, the inventors of the present application have found a technology for improving the characteristics of a lead-acid battery by a completely different approach from the conventional one. The present invention is based on this new knowledge.

[0018] When a conventional separator containing a synthetic fiber nonwoven fabric and a glass fiber mat is used, the cycle characteristics may be insufficient. During charge / discharge cycles, the electrolyte in the separator is likely to decrease due to expansion and contraction of the synthetic fiber nonwoven fabric and gas generation from the electrodes. Since the synthetic fiber nonwoven fabric has a lower electrolyte retention capacity than the glass fiber mat, the electrolyte in the synthetic fiber nonwoven fabric is particularly likely to decrease. As a result, it is believed that the characteristics of the lead-acid battery are significantly reduced.

[0019] As a result of the study, the inventors of the present application found that the characteristics (cycle life, etc.) of the lead-acid battery can be significantly improved by setting the ratio Vf / Vg in the range of 0.5 to 1.2. That is, in this embodiment, the proportion Vf of relatively small pores in the nonwoven fabric (F) does not differ significantly from the proportion Vg of relatively small pores in the glass fiber mat. Therefore, even if charge-discharge cycles are performed, it is considered that the balance between the amount of electrolyte held in the nonwoven fabric (F) and the amount of electrolyte held in the glass fiber mat is maintained. As a result, it is presumed that a significant decrease in battery performance due to charge-discharge cycles is suppressed. By maintaining the amount of electrolyte in the nonwoven fabric (F), an increase in internal resistance can be suppressed. By suppressing the increase in internal resistance, an increase in IR drop during high-rate discharge is suppressed, and the discharge capacity during high-rate discharge is maintained. Therefore, suppressing the increase in internal resistance is particularly effective in improving cycle characteristics accompanying high-rate discharge.

[0020] The ratio Vf / Vg may be 0.50 or more, 0.53 or more, 0.65 or more, 0.79 or more, or 0.86 or more. The ratio Vf / Vg may be 1.20 or less, 1.18 or less, 1.12 or less, 1.00 or less, or 0.86 or less. These lower and upper limits can be combined arbitrarily as long as there is no contradiction. For example, the ratio Vf / Vg may be in the range of 0.50 to 1.20, the range of 0.53 to 1.20, the range of 0.65 to 1.20, the range of 0.79 to 1.20, or the range of 0.86 to 1.20. With regard to these ranges, the upper limit may be replaced with 1.18, 1.12, 1.00, or 0.86 as long as the upper limit is not equal to or less than the lower limit.

[0021] The ratio Vf / Vg is preferably in the range of 0.71 to 1.18. With this configuration, the life characteristics in charge-discharge cycles involving high-rate discharge can be particularly improved.

[0022] The ratio Vf / Vg can be changed by changing Vf and / or Vg. Vf may be changed, for example, by changing the diameter of the organic fibers constituting the nonwoven fabric (F) and / or the surface density (mass per unit area) of the nonwoven fabric (F). Vf can be increased by decreasing the diameter of the organic fibers, and Vf can be decreased by increasing the diameter of the organic fibers. Also, Vf can be increased by increasing the surface density of the nonwoven fabric (F), and Vf can be decreased by decreasing the surface density.

[0023] Similarly, Vg may be changed by changing the diameter of the glass fibers constituting the glass fiber mat and / or the surface density (mass per unit area) of the glass fiber mat. Vg can be increased by decreasing the diameter of the glass fibers, and Vg can be decreased by increasing the diameter of the glass fibers. Also, Vg can be increased by increasing the surface density of the glass fiber mat, and Vg can be decreased by decreasing the surface density.

[0024] The Vf of the nonwoven fabric (F) may be 35% or more, 55% or more, or 73% or more. Vf may be 100% or less, 95% or less, 85% or less, 73% or less, or 55% or less. These lower and upper limits can be combined arbitrarily as long as there is no contradiction. For example, Vf may be in the range of 35 to 100%, 55 to 100%, or 73 to 100%. The upper limit of these ranges may be replaced with 95%, 85%, 73%, or 55%, as long as it is not below the lower limit.

[0025] The average thickness of the nonwoven fabric (F) may be in the range of 0.05 mm to 0.5 mm (for example, in the range of 0.1 mm to 0.3 mm). By making the average thickness of the nonwoven fabric (F) 0.1 mm or more, the effect of preventing short circuits can be enhanced. By making the average thickness of the nonwoven fabric (F) 0.3 mm or less, the internal resistance can be reduced.

[0026] Each of the positive plates may include a positive current collector including an expanded lattice portion (first expanded lattice portion), and each of the negative plates may include a negative current collector including an expanded lattice portion (second expanded lattice portion). The first expanded lattice portion and the second expanded lattice portion may each be a lattice body without a frame around it. Since the expanded lattice portion is easily bent, it is particularly important to prevent short circuits. In particular, a lattice body without a frame around it is prone to short circuits around the positive and negative plates due to the expansion of the electrode material. Therefore, when a current collector including an expanded lattice portion is used, it is preferable to house the positive and / or negative plates in a bag made of a nonwoven fabric (F).

[0027] The organic fiber may include split fibers including acrylic fibers. By using split fibers, it becomes easier to increase the ratio Vf / Vg. By using acrylic fibers, it is possible to increase the liquid retention.

[0028] The acrylic fiber is a fiber (acrylonitrile fiber) formed by using a polymer (acrylonitrile polymer) containing acrylonitrile units. The acrylonitrile polymer may contain only acrylonitrile units as a constituent unit. Alternatively, the acrylonitrile polymer may be a copolymer containing acrylonitrile units and other monomer units. The other monomer units may be one type or two or more types. The proportion of acrylonitrile units in the polymer may be, for example, 50% by mass or more, 70% by mass or more, 80% by mass or more, or 85% by mass or more. Examples of other monomers copolymerized with acrylonitrile include acrylic acid, methacrylic acid, derivatives thereof, olefin monomers (vinyl acetate, vinyl chloride, vinylidene chloride, etc.), and the like. The acrylic fiber includes acrylic fibers.

[0029] The split fibers containing acrylic fibers may be commercially available split fibers or may be synthesized by a known method. The split fibers containing acrylic fibers may be formed, for example, by spinning composite fibers containing an acrylic fiber portion and another fiber portion. The polymer constituting the other fiber of the composite fiber may be a known polymer (polyethylene, polypropylene, other polymers). The nonwoven fabric (F) may be formed as follows. First, a sheet is obtained by papermaking fibers containing composite fibers. Next, a high-pressure water stream is sprayed onto the sheet to entangle the fibers and simultaneously split the composite fibers. In this way, a nonwoven fabric (F) containing split fibers (for example, split fibers of acrylic fibers) is obtained.

[0030] The organic fibers constituting the nonwoven fabric (F) may include organic fibers formed by the release of a component in the electrolyte from fibers containing the component in the electrolyte. By using such organic fibers, it becomes easy to increase the ratio Vf / Vg. The nonwoven fabric (F) used in the manufacture of a lead-acid battery may include organic fibers containing the component, or may be composed only of organic fibers containing the component. When a lead-acid battery is manufactured using such a nonwoven fabric (F), the component will release from the organic fibers over time. The release of the component can increase the proportion of fine pores. The component released in the electrolyte may be a component that dissolves during electrolysis, or a component that decomposes in the electrolyte and releases from the organic fibers. Examples of such components include acetate. For the organic fibers containing such components, commercially available fibers may be used, or they may be synthesized by a known method.

[0031] The first separator may include a plurality of bags made of nonwoven fabric (F). In this case, one of the electrodes selected from the plurality of positive electrode plates and the plurality of negative electrode plates may be housed in the bag. The bag made of nonwoven fabric (F) is, for example, a bag having three sides closed and one side open. The bag may be formed, for example, by overlapping the nonwoven fabric (F) and heat welding at predetermined locations. The positive electrode plate and / or the negative electrode plate can be inserted from the open side of the bag.

[0032] The second separator may include a plurality of U-shaped cross-section mats made of glass fiber mats. The bags housing the one electrode plates may be disposed inside the U-shaped cross-section mat. Alternatively, the other electrode plates other than the one electrode plate may be disposed inside the U-shaped cross-section mat. The U-shaped cross-section mat may be simply referred to as a "U-shaped mat" below. From another perspective, the U-shaped cross-section mat is a mat folded in two.

[0033] The lead-acid battery of this embodiment may be a valve-regulated lead-acid battery or other lead-acid batteries (such as a flooded lead-acid battery). The valve-regulated type has the advantage of not requiring water replenishment. On the other hand, repeated charging and discharging can easily cause a problem in that the electrolyte gradually decreases and the internal resistance increases. In general, when a separator made of a laminate of an organic fiber nonwoven fabric and a glass fiber mat is used, the amount of electrolyte in the organic fiber nonwoven fabric is likely to decrease significantly due to the decrease in the electrolyte. Therefore, in the case of a valve-regulated lead-acid battery, the configuration of this embodiment is particularly preferable.

[0034] A plurality of positive plates, a plurality of negative plates, and a separator constitute an electrode plate group. A plurality of positive plates and a plurality of negative plates are alternately arranged in the order of negative plate / positive plate / negative plate / positive plate. That is, the positive plates and the negative plates are usually arranged alternately one by one. The number of positive plates and the number of negative plates may be different. Usually, the number of one of the positive plates and the negative plates is one more than the other. For example, the number of positive plates may be one more than the number of negative plates. Alternatively, the number of negative plates may be one more than the number of positive plates. In these cases, the more number of plates may be arranged at both ends of the electrode plate group. There is no limitation on the number of positive plates and negative plates. The number of positive plates and the number of negative plates may be independently in the range of 2 to 20 (for example, in the range of 3 to 16).

[0035] Between the positive electrode plate and the negative electrode plate adjacent to the positive electrode plate, a nonwoven fabric (F) and a glass fiber mat are arranged so as to be laminated. These may be arranged in the order of positive electrode plate / nonwoven fabric (F) / glass fiber mat / negative electrode plate. Alternatively, they may be arranged in the order of positive electrode plate / glass fiber mat / nonwoven fabric (F) / negative electrode plate.

[0036] In a preferred example, a first separator including a plurality of bags of nonwoven fabric (F) and a second separator including a plurality of U-shaped mats are used. First to fourth examples of the arrangement of the separator in this case are described below. In the first example, the positive electrode plate is accommodated in a bag of nonwoven fabric (F), and the bag is arranged inside the U-shaped mat. The negative electrode plate is not arranged inside the bag of nonwoven fabric (F) and inside the U-shaped mat. In the second example, the negative electrode plate is accommodated in a bag of nonwoven fabric (F), and the bag is arranged inside the U-shaped mat. The positive electrode plate is not arranged inside the bag of nonwoven fabric (F) and inside the U-shaped mat. In the third example, the positive electrode plate is accommodated in a bag of nonwoven fabric (F), and the negative electrode plate is arranged inside the U-shaped mat. In the fourth example, the negative electrode plate is accommodated in a bag of nonwoven fabric (F), and the positive electrode plate is arranged inside the U-shaped mat.

[0037] As long as the nonwoven fabric (F) and the glass fiber mat are arranged so as to be laminated between the positive electrode plate and the negative electrode plate adjacent to the positive electrode plate, the configuration of the electrode plate group is not limited to the above configuration. The form of the nonwoven fabric (F) and the form of the glass fiber mat may be any of a sheet, a bag, and a U-shaped cross section, independently of each other.

[0038] (Evaluation of the ratio Vf / Vg) The Vf (%) of the nonwoven fabric (F) and the Vg (%) of the glass fiber mat are measured by pore analysis using mercury intrusion porosimetry. The ratio Vf / Vg can be calculated from the measured Vf and Vg. The ratios Vf and Vg may be measured using unused separators (first and second separators). Alternatively, the ratios Vf and Vg may be measured using separators removed from a lead-acid battery.

[0039] When the separators (first and second separators) are removed from the lead-acid battery for measurement, the separators are removed from the lead-acid battery in a fully charged state. The separators removed from the lead-acid battery are washed and dried prior to measurement. The washing and drying are performed in the following procedure. First, the separator removed from the lead-acid battery is immersed in pure water (cleaning solution) for one hour, thereby removing sulfuric acid from the separator. Next, the separator is removed from the cleaning solution and left to stand in an environment at 25°C for 16 hours or more to dry it. Measurements are performed on the separators obtained in this manner.

[0040] Specifically, the Vf of the nonwoven fabric (F) is measured as follows. First, a part of the nonwoven fabric (F) constituting the first separator (for example, the vicinity of the center part not welded) is cut to a size of 100 mm x 100 mm to obtain a sample. The pore distribution of the obtained sample is measured using a mercury porosimeter (Shimadzu Corporation, Autopore IV9510). From the measured pore distribution, Vf is obtained. The measurement pressure range is 0.5 psia (3447 Pa) to about 60,000 psia (about 419 MPa). 0.5 psia (3447 Pa) corresponds to a pore with a diameter of 360 μm. About 60,000 psia (about 419 MPa) corresponds to a pore with a diameter of 0.003 μm. Therefore, the above pressure range corresponds to a pore diameter range of 0.003 μm to 360 μm.

[0041] Specifically, the Vg of the glass fiber mat is measured as follows. First, a part of the glass fiber mat constituting the second separator (for example, a part in contact with the vicinity of the center of the electrode plate) is cut to a size of 10 mm x 10 mm to obtain a sample. Except for using the sample, the pore distribution of the sample is measured under the same conditions as those for measuring the pore distribution of the nonwoven fabric (F). Vg is determined from the measured pore distribution.

[0042] (Average thickness of nonwoven fabric (F)) The average thickness of the nonwoven fabric (F) is the average value of the thicknesses at 10 arbitrarily selected equally spaced points. The thickness at each point is measured, for example, using an outside micrometer (0 to 25 mm) as specified in JIS B7502:2016 (micrometer).

[0043] The fully charged state of a flooded lead-acid battery is defined by JIS D 5301:2019. More specifically, the fully charged state is defined as a state in which the lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) 0.2 times the value (unit: Ah) listed as the rated capacity until the terminal voltage (V) during charging or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is defined as a state in which constant-current constant-voltage charging of 2.23 V / cell is performed in an air tank at 25°C ± 2°C with a current (A) 0.2 times the value (unit: Ah) listed as the rated capacity, and charging is terminated when the charging current during constant-voltage charging becomes 0.005 times the value (unit: Ah) listed as the rated capacity.

[0044] A fully charged lead-acid battery refers to a fully charged lead-acid battery that has already been formed. A lead-acid battery may be fully charged immediately after formation, or after a period of time has passed since formation (for example, a lead-acid battery that is in use (preferably in the early stages of use) after formation may be fully charged).

[0045] An example of the configuration of the lead acid battery of the present invention will be described below. The components described below may be the same as those described above. Known components may be used for components other than those characteristic of the present invention.

[0046] (Separator) The separator includes a first separator including a nonwoven fabric (F) made of organic fibers, and a second separator including a glass fiber mat. The first separator may be mostly (e.g., 80% by mass or more) made of the nonwoven fabric (F), or may be made only of the nonwoven fabric (F). The second separator may be mostly (e.g., 80% by mass or more) made of the glass fiber mat, or may be made only of the glass fiber mat.

[0047] (Non-woven fabric (F)) The nonwoven fabric (F) is made of organic fibers. 70% by mass or more (e.g., 80% by mass or more, 90% by mass or more, or 95% by mass or more) of the first separator is organic fibers. The first separator may be made of only organic fibers. Examples of organic fibers include synthetic fibers (polyolefin fibers, acrylic fibers, polyester fibers, etc.) and fibers containing naturally derived components. Examples of polyolefin fibers include polyethylene fibers and polypropylene fibers. Examples of polyester fibers include polyethylene terephthalate fibers. Examples of fibers containing naturally derived components include pulp fibers (e.g., cellulose fibers). The first separator may contain components other than organic fibers, such as acid-resistant inorganic powders and polymers as binders.

[0048] In order to increase the permeability of the electrolyte into the fine pores and the retention of the electrolyte in the pores, it is preferable that the hydrophilicity of the organic fiber is high. From this viewpoint, it is preferable to use an organic fiber having a higher hydrophilicity than polyolefin fiber that has not been hydrophilized. For example, a polymer (e.g., a copolymer) using a monomer containing a hydrophilic group (such as a hydroxyl group or a carboxyl group) may be used, or an organic fiber that has been hydrophilized may be used. A known hydrophilization treatment may be used for the hydrophilization treatment. Examples of organic fibers having a higher hydrophilicity than polyolefin fiber that has not been hydrophilized include acrylic fibers and polyethylene terephthalate fibers (PET fibers). One example of a preferable organic fiber is a copolymer synthesized using a monomer containing a hydrophilic group and acrylonitrile.

[0049] The organic fiber may be a split fiber. By using the split fiber, it becomes easier to increase the ratio Vf.

[0050] Among the organic fibers constituting the nonwoven fabric (F), the average fiber diameter of the split fibers may be in the range of 0.01 μm to 1.0 μm (for example, in the range of 0.01 μm to 0.75 μm). The average fiber diameter of the organic fibers constituting the nonwoven fabric (F) may be in the range of 0.5 μm to 15 μm (for example, in the range of 0.5 μm to 10 μm). By setting the average fiber diameter to 9 μm or less, it becomes easier to increase the ratio Vf. The average fiber diameter of the organic fibers can be calculated by calculating the maximum diameter of any cross section perpendicular to the length direction for any 100 fibers, and averaging the 100 values. Note that, for split fibers, each fiber after splitting is treated as one fiber. For example, a split fiber divided into 10 fibers is treated as 10 fibers.

[0051] The surface density of the nonwoven fabric (F) is 40 g / m 2 ~90g / m 2 range (e.g. 50g / m 2 ~80g / m 2 The average fiber diameter of the organic fibers constituting the nonwoven fabric (F) may be in the range of 0.5 μm to 10 μm, and the surface density of the nonwoven fabric (F) may be in the range of 50 g / m 2 ~80g / m 2 By setting the range, it becomes easier to increase the ratio Vf.

[0052] (fiberglass mat) The glass fiber mat is, for example, a sheet (e.g., nonwoven fabric) formed using glass fibers. The entire glass fiber mat may be formed of glass fibers. Alternatively, the glass fiber mat may contain glass fibers as a main component. The glass fiber content in the second separator may be 90 mass % or more, or 95 mass % or more. The second separator may contain components other than glass fibers, such as organic fibers, acid-resistant inorganic powder, and polymers as binders, and the content thereof is usually 20 mass % or less (e.g., 10 mass % or less, 5 mass % or less).

[0053] The average fiber diameter of the glass fibers may be in the range of 0.1 μm to 30 μm, or in the range of 0.5 μm to 15 μm. The average fiber diameter of the glass fibers can be calculated by determining the maximum diameter of any cross section perpendicular to the length direction of any 100 fibers and averaging the values ​​of the 100 fibers.

[0054] The surface density of the glass fiber mat is 100 g / m 2 ~250g / m 2 range (e.g. 100g / m 2 ~200g / m 2 The range may be within 100%.

[0055] (Positive plate) The positive plate includes a positive current collector and a positive electrode material disposed on the positive current collector. The positive electrode material is held by the positive current collector. The positive electrode material is the positive plate excluding the positive current collector. The positive current collector can be formed by casting lead or a lead alloy or by processing a lead or lead alloy sheet. Examples of processing methods include expanding and punching.

[0056] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Ca-based alloy and Pb-Ca-Sn-based alloy are preferable. The positive electrode current collector may have lead alloy layers with different compositions, or the alloy layers may be multiple. For the core metal, it is preferable to use Pb-Ca-based alloy or Pb-Sb-based alloy.

[0057] The positive electrode material contains a positive electrode active material (lead dioxide or lead sulfate) that exhibits capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.

[0058] The positive electrode plate may be prepared by the following method. First, a positive electrode current collector is filled with a positive electrode paste, and the positive electrode paste is aged and dried to prepare an unformed positive electrode plate. The unformed positive electrode plate is then formed to obtain a positive electrode plate. The positive electrode paste is prepared by mixing materials including lead powder, additives, water, and sulfuric acid.

[0059] (Negative plate) The negative plate of a lead-acid battery is composed of a negative current collector and a negative electrode material. The negative electrode material is the portion of the negative plate excluding the negative current collector.

[0060] The negative electrode current collector may be formed by casting lead or a lead alloy, or by processing a lead or lead alloy sheet, for example by expanding or punching.

[0061] The lead alloy used in the negative electrode current collector may be any of Pb-Sb based alloys, Pb-Ca based alloys, and Pb-Ca-Sn based alloys. These lead or lead alloys may further contain other additive elements, and may contain at least one element selected from the group consisting of Ba, Ag, Al, Bi, As, Se, and Cu.

[0062] The negative electrode material includes a negative electrode active material (lead or lead sulfate) that exhibits capacity through an oxidation-reduction reaction. The negative electrode material may include a shrinkage inhibitor, a carbonaceous material (such as carbon black), barium sulfate, etc. The negative electrode material may include other additives as necessary.

[0063] The negative active material in the charged state is sponge lead, but the unformed negative plate is usually made from lead powder.

[0064] The negative electrode plate may be prepared by the following method. First, a negative electrode current collector is filled with a negative electrode paste, and the paste is aged and dried to prepare an unformed negative electrode plate. The unformed negative electrode plate is then chemically formed to obtain a negative electrode plate. The negative electrode paste can be prepared, for example, by adding water and sulfuric acid to a material containing lead powder, an organic shrinkage inhibitor, and various additives as necessary, and kneading the mixture. In the aging step, it is preferable to age the unformed negative electrode plate in an environment that is higher than room temperature and has a high humidity.

[0065] The formation may be performed by immersing the plate group including the unformed negative plate in an electrolyte solution containing sulfuric acid in a battery container of the lead-acid battery and charging the plate group. The formation may be performed before assembling the lead-acid battery or before assembling the plate group. The formation produces spongy lead.

[0066] (electrolyte) The electrolytic solution is an aqueous solution containing sulfuric acid, and may contain at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions. The electrolytic solution may be gelled as necessary.

[0067] The specific gravity of the electrolyte at 20°C is, for example, 1.10 g / cm 3 The specific gravity of the electrolyte at 20°C is 1.35 g / cm 3 Note that these specific gravities are values ​​for the electrolyte of a lead-acid battery that is already formed and in a fully charged state.

[0068] (Exterior body) The lead-acid battery includes an exterior body. The exterior body may include a battery case that contains a plate group and an electrolyte, and a lid that covers an opening of the battery case. The battery case may include a plurality of cell chambers. One plate group may be disposed in one cell chamber. When the lead-acid battery is a valve-regulated lead-acid battery (VRLA battery), the exterior body includes a control valve. The control valve is usually disposed in the lid. The control valve opens when the internal pressure of the exterior body becomes high (for example, when it reaches or exceeds a predetermined value) to release gas within the exterior body to the outside. The control valve may be a known control valve used in lead-acid batteries.

[0069] Examples of embodiments according to the present invention will be described below with reference to the drawings. The above-mentioned components can be applied to the components of the examples described below. The examples described below can be modified based on the above description. The matters described below may be applied to the above-mentioned embodiments. In the embodiments described below, components that are not essential for the lead-acid battery of the present invention may be omitted.

[0070] Fig. 1 is a cross-sectional view showing a schematic diagram of a portion of the structure of an example of a valve-regulated lead-acid battery. The lead-acid battery 1 shown in Fig. 1 includes a plate group 30, an electrolyte (not shown), and an exterior body (a battery case 10 and a lid 12). The battery case 10 contains the plate group 30 and the electrolyte. The upper opening of the battery case 10 is sealed by the lid 12.

[0071] The battery container 10 is divided into multiple (three in the example of FIG. 1) mutually independent cell chambers 10R. Each cell chamber 10R contains one electrode plate group 30. The lid 12 has an independent exhaust valve (control valve) 13 for each cell chamber 10R. When the internal pressure of the cell chamber 10R exceeds a predetermined upper limit, the exhaust valve 13 opens and releases some of the gas in the cell chamber 10R to the outside. When the internal pressure of the cell chamber 10R is equal to or lower than the upper limit, the exhaust valve 13 is closed, and oxygen generated in the positive electrode plate 31 is reduced in the negative electrode plate 32 in the same cell chamber 10R to produce water.

[0072] The structure of the valve-regulated lead-acid battery is not limited to the above. Fig. 1 shows an example in which an exhaust valve 13 is arranged in each cell chamber 10R. However, the valve-regulated lead-acid battery may have a structure in which the number of exhaust valves 13 is less than the number of cell chambers 10R. In that case, the lid of the valve-regulated lead-acid battery may have a collective exhaust chamber that communicates with each cell chamber. The collective exhaust chamber may have a smaller number of exhaust valves (for example, one) than the number of cell chambers.

[0073] A cross-sectional view of an example of an electrode plate assembly 30 is shown in FIG. 2. In the following figures, the positive electrode current collector and the negative electrode current collector are omitted. The electrode plate assembly 30 in FIG. 2 includes a positive electrode plate 31, a negative electrode plate 32, and a separator 40. The separator 40 includes a first separator 41 including a nonwoven fabric (F) and a second separator 42 including a glass fiber mat. The nonwoven fabric (F) constituting the first separator 41 has the above-mentioned characteristics.

[0074] The first separator 41 includes a plurality of bags 41a made of nonwoven fabric (F). Each bag 41a houses one positive electrode plate 31. The bag 41a may be formed by folding a nonwoven fabric (F) having a size approximately twice that of the positive electrode plate 31 in the center and bonding the two overlapping sides. The bonding of the two sides may be performed, for example, by welding using heat.

[0075] The second separator 42 includes a plurality of U-shaped mats (mats with a U-shaped cross section) 42a made of a glass fiber mat. A bag 41a and a positive electrode plate 31 housed therein are disposed inside each of the U-shaped mats 42a.

[0076] The U-shaped mat 42a is formed by folding one mat at the folding portion 42b. The U-shaped mat 42a has a U-shaped cross section (the cross section shown in FIG. 1). The cross section is perpendicular to the direction in which the folding portion 42b extends. From another perspective, the U-shaped mat 42a is a mat that is folded at the folding portion 42b and then stacked. The inside of the U-shaped mat 42a means the space between two sheet-like portions connected via the folding portion 42b.

[0077] An upwardly protruding current collecting lug (not shown) is provided on the upper portion of each of the plurality of negative electrode plates 32. An upwardly protruding current collecting lug (not shown) is also provided on the upper portion of each of the plurality of positive electrode plates 31. The lugs of the negative electrode plates 32 are connected and integrated with each other by a negative electrode strap (not shown). Similarly, the lugs of the positive electrode plates 31 are connected and integrated with each other by a positive electrode strap (not shown). The negative electrode strap is connected to a negative electrode pole (not shown) that serves as an external terminal. The positive electrode strap is connected to a positive electrode pole (not shown) that serves as an external terminal.

[0078] The electrode plate group 30 is configured by alternately arranging the positive electrode plates 31 and the negative electrode plates 32 housed in the bag 41a and the U-shaped mat 42a. As a result, the nonwoven fabric (F) and the glass fiber mat are arranged so as to be laminated between the positive electrode plate 31 and the negative electrode plate 32 adjacent to the positive electrode plate 31. FIG. 2 shows an electrode plate group 30 including five positive electrode plates 31 and six negative electrode plates 32. The number of the negative electrode plates 32 is one more than the number of the positive electrode plates 31. The negative electrode plates 32 are arranged at both ends of the electrode plate group 30. As described above, the number of the positive electrode plates 31 and the number of the negative electrode plates 32 can be changed. Furthermore, the position of the positive electrode plate 31 and the position of the negative electrode plate 32 may be interchanged. That is, the negative electrode plate 32 may be housed in the bag 41a and the U-shaped mat 42a.

[0079] A cross-sectional view of another example of the electrode plate group 30 is shown in Fig. 3. The electrode plate group 30 shown in Fig. 3 differs from the electrode plate group 30 shown in Fig. 2 only in the arrangement of the positive electrode plates 31, the negative electrode plates 32, and the separators 40, and therefore a duplicated description will be omitted.

[0080] In the electrode plate group 30 shown in FIG. 3, the positive electrode plate 31 is disposed inside the U-shaped mat 42a, and the negative electrode plate 32 is housed in the bag 41a. The positive electrode plate 31 housed in the U-shaped mat 42a and the negative electrode plate 32 housed in the bag 41a are arranged alternately. The number of the negative electrode plates 32 is one more than the number of the positive electrode plates 31. The negative electrode plates 32 are disposed at both ends of the electrode plate group 30. As described above, the number of the positive electrode plates 31 and the number of the negative electrode plates 32 can be changed. In addition, the positive electrode plates 31 and the negative electrode plates 32 may be interchanged. That is, the negative electrode plate 32 may be disposed inside the U-shaped mat 42a, and the positive electrode plate 31 may be housed in the bag 41a.

[0081] In the electrode plate group 30, on the straight line connecting the positive electrode material of any positive electrode plate 31 and the negative electrode material of the negative electrode plate 32 adjacent to that positive electrode plate 31, there is a laminate of the nonwoven fabric (F) and the glass fiber mat.

[0082] The lead-acid battery according to the present invention will be described below.

[0083] (1) a plurality of positive electrode plates and a plurality of negative electrode plates arranged alternately; A separator; An electrolyte. the separator includes a first separator including a nonwoven fabric made of organic fibers and a second separator including a glass fiber mat; the nonwoven fabric and the glass fiber mat are arranged so as to be laminated between the positive electrode plate and the negative electrode plate adjacent to the positive electrode plate, When the pores Pf of the nonwoven fabric are measured by mercury intrusion porosimetry, the ratio of the volume of the pores Pf having a diameter in the range of 0.01 μm to 15.0 μm to the volume of all the pores Pf is Vf (%); When the pores Pg of the glass fiber mat are measured by mercury intrusion porosimetry, the ratio of the volume of the pores Pg having a diameter in the range of 0.01 μm to 15.0 μm to the volume of all the pores Pg is Vg (%); A lead-acid battery with a Vf / Vg ratio in the range of 0.5 to 1.2.

[0084] (2) The lead-acid battery according to (1) above, wherein the ratio Vf / Vg is in the range of 0.71 to 1.18.

[0085] (3) The lead-acid battery according to (1) or (2) above, wherein the nonwoven fabric has an average thickness in the range of 0.1 mm to 0.3 mm.

[0086] (4) The lead-acid battery according to any one of (1) to (3) above, wherein each of the positive electrode plates includes a positive electrode current collector including a first expanded lattice portion, and each of the negative electrode plates includes a negative electrode current collector including a second expanded lattice portion.

[0087] (5) The lead-acid battery according to any one of (1) to (4) above, wherein the organic fibers include split fibers containing acrylic fibers.

[0088] (6) The lead-acid battery according to any one of (1) to (5), wherein the organic fibers include organic fibers formed by dissociating a component that dissociates in the electrolytic solution from fibers that contain the component in the electrolytic solution.

[0089] (7) The lead-acid battery according to any one of (1) to (6), wherein the first separator includes a plurality of bags made of the nonwoven fabric, and each of the plurality of positive electrode plates and one of the plurality of negative electrode plates is housed in the bag.

[0090] (8) The lead-acid battery according to (7) above, wherein the second separator includes a plurality of mats each having a U-shaped cross section made of the glass fiber mat, and the bags housing each of the one electrode plates are disposed inside the mats each having a U-shaped cross section.

[0091] (9) The lead-acid battery according to (7) above, wherein the second separator includes a plurality of mats each having a U-shaped cross section formed of the glass fiber mat, and each of the other electrode plates that is not one of the electrode plates is disposed inside the U-shaped cross section mat.

[0092] (10) The lead-acid battery according to any one of (1) to (9) above, which is a valve regulated lead-acid battery.

[0093] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0094] (Production of lead-acid batteries A1 to A12 and C1 to C3) Lead acid batteries A1 to A12 and C1 to C3 were produced by the following method. (a) Preparation of the negative electrode plate The raw material lead powder, lignin as an organic shrinkage inhibitor, barium sulfate, and carbon black were mixed with an appropriate amount of sulfuric acid aqueous solution to obtain a negative electrode paste. The materials were mixed so that the organic shrinkage inhibitor content was 0.1 mass%, the barium sulfate content was 0.4 mass%, and the carbon black content was 0.2 mass%. Next, the negative electrode paste was filled into the mesh part of an expanded lattice made of Pb-Ca-Sn alloy, and further aged and dried to obtain an unformed negative electrode plate.

[0095] (b) Preparation of the positive electrode plate A positive electrode paste was obtained by mixing the raw lead powder and an aqueous sulfuric acid solution. The positive electrode paste was filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, and then aged and dried to obtain an unformed positive electrode plate.

[0096] (c) Preparation of the separator As the separator, a bag-shaped separator (bag-shaped separator) formed by using a nonwoven fabric of organic fibers containing acrylic fibers and a U-shaped mat formed by using a glass fiber mat were prepared. In this example, a plurality of lead-acid batteries shown in Table 1 were produced by selecting a separator and a glass fiber mat so that the above-mentioned values ​​of Vf, Vg, and Vf / Vg were changed. In this example, Vf was changed by changing the proportion and type of split fibers in the total fibers constituting the nonwoven fabric. Specifically, when Vf was increased, the split fibers were increased compared to single fibers, and / or the proportion of acetate contained in the split fibers was set to 3 mass% or more. Vg was changed by changing the fiber diameter of the glass fibers. Specifically, when Vg was increased, the fiber diameter of the glass fibers was reduced.

[0097] In the manufacture of the lead-acid battery shown in Table 1, the average fiber diameter of the organic fibers used in the nonwoven fabric was changed in the range of 0.5 to 15 μm. The surface density of the nonwoven fabric was changed in the range of 40 to 90 g / m 2 The average fiber diameter of the glass fibers constituting the U-shaped mat was changed in the range of 0.1 to 30 μm. The surface density of the glass fibers was changed in the range of 100 to 200 g / m.

[0098] (d) Preparation of lead-acid battery The lead-acid batteries were fabricated to have a rated voltage of 12V and a rated 3-hour rate capacity of 60Ah. One electrode plate group of the lead-acid battery includes 11 positive electrode plates and 12 negative electrode plates. Each positive electrode plate was housed in a pouch-shaped separator, which was then placed inside a U-shaped mat. Next, the negative electrode plates and the positive electrode plates housed in the separator were alternately stacked to form an electrode plate group. The electrode plate group was housed in a polypropylene battery case together with an electrolyte (aqueous sulfuric acid solution), and chemical formation was performed in the battery case. In this way, valve-regulated lead-acid batteries (batteries A1 to A12 and C1 to C3) were fabricated. The specific gravity of the electrolyte in the fully charged lead-acid battery at 20°C was 1.28.

[0099] (Evaluation of the Vf / Vg ratio of the lead-acid battery) The separator was removed from the fully charged lead acid battery, and Vf and Vg were measured by the above-mentioned method, and the ratio Vf / Vg was calculated.

[0100] (Evaluation of cycle life of the produced lead-acid battery) The lead-acid battery thus produced was subjected to a charge-discharge cycle including a high-rate discharge to evaluate the cycle life at high-rate discharge. In the charge-discharge cycle, discharge was performed for 13 minutes at a discharge current of 150A. Charging was performed using a five-stage constant current charging method. Specifically, charging was performed in the following manner. First, constant current charging was performed at 0.2CA, and when the charging voltage reached the switching voltage, the charging current was reduced to 0.1CA. The charging voltage was reduced by reducing the charging current, but when the charging voltage reached the switching voltage again, the charging current was reduced to 0.05CA. When the charging voltage reached the switching voltage again, the charging current was reduced to 0.025CA. When the charging voltage reached the switching voltage again, charging was continued for 2.5 hours while maintaining the charging current at 0.025CA. In this manner, five stages of charging were performed. The switching voltage was set to 14.4V. Note that 1C means the current (A) of the numerical value (Ah) listed as the rated capacity.

[0101] The discharge capacity was measured at the beginning of the charge / discharge cycle and every 25 cycles when the battery was discharged at a discharge current of 150 A until the battery voltage reached 8.4 V. The number of cycles when the discharge capacity reached 80% of the initial discharge capacity was taken as the number of life cycles. The number of life cycles of battery C3 was taken as 100%, and the number of life cycles of the other batteries was evaluated relatively.

[0102] The evaluation results of the lead-acid batteries are shown in Table 1. The separators and glass fiber mats used in the manufacture of the batteries C1 to C3 were conventional separators and glass fiber mats.

[0103] [Table 1]

[0104] The data in Table 1 is shown in Figure 4. As shown in Table 1 and Figure 4, when the ratio Vf / Vg is in the range of 0.5 to 1.2, the cycle life is significantly improved. In terms of further improving the cycle life, the ratio Vf / Vg is preferably in the range of 0.71 to 1.18, and more preferably in the range of 0.79 to 1.12. [Industrial Applicability]

[0105] The present invention can be used in lead-acid batteries, for example, in valve-regulated lead-acid batteries. The valve-regulated lead-acid battery of the present invention may be used as a stationary valve-regulated lead-acid battery such as an uninterruptible power supply (UPS), but its use is not particularly limited. [Explanation of symbols]

[0106] 1:Lead acid battery 10: Battery case 10R: Cell room 12: Lid 13: Exhaust valve 30: Plate group 31: Positive electrode plate 32: Negative plate 40: Separator 41: First separator 41a: Bag 42: Second separator 42a: U-shaped mat 42b: Bending part

Claims

1. A plurality of alternating positive and negative electrode plates; A separator; An electrolyte. the separator includes a first separator including a nonwoven fabric made of organic fibers and a second separator including a glass fiber mat; the nonwoven fabric and the glass fiber mat are arranged so as to be laminated between the positive electrode plate and the negative electrode plate adjacent to the positive electrode plate, When the pores Pf of the nonwoven fabric are measured by mercury intrusion porosimetry, the ratio of the volume of the pores Pf having a diameter in the range of 0.01 μm to 15.0 μm to the volume of all the pores Pf is Vf (%); When the pores Pg of the glass fiber mat are measured by mercury intrusion porosimetry, the ratio of the volume of the pores Pg having a diameter in the range of 0.01 μm to 15.0 μm to the volume of all the pores Pg is Vg (%); The Vg(%) is in the range of 60.0 to 85.0%, A lead-acid battery having a ratio Vf / Vg in the range of 0.5 to 1.

2.

2. The lead-acid battery according to claim 1, wherein the ratio Vf / Vg is in the range of 0.71 to 1.

18.

3. The lead-acid battery according to claim 1 or 2, wherein the nonwoven fabric has an average thickness in the range of 0.1 mm to 0.3 mm.

4. Each of the plurality of positive electrode plates includes a positive electrode current collector including a first expanded lattice portion, The lead-acid battery according to any one of claims 1 to 3, wherein each of the plurality of negative electrode plates includes a negative electrode current collector including a second expanded lattice portion.

5. The lead acid battery according to any one of claims 1 to 4, wherein the organic fibers include split fibers containing acrylic fibers.

6. The organic fiber includes an organic fiber formed by releasing a component from a fiber containing the component that is released in the electrolyte in the electrolyte. The lead acid battery according to any one of claims 1 to 5.

7. the first separator includes a plurality of bags made of the nonwoven fabric, The lead-acid battery according to any one of claims 1 to 6, wherein each of the plurality of positive electrode plates and the plurality of negative electrode plates is housed in the bag.

8. The second separator includes a plurality of U-shaped cross-section mats made of the glass fiber mat, The lead-acid battery according to claim 7 , wherein the bag housing each of the one electrodes is disposed inside the U-shaped cross-section mat.

9. The second separator includes a plurality of U-shaped cross-section mats made of the glass fiber mat, The lead-acid battery according to claim 7 , wherein each of the one electrode plates that is not the other electrode plate is disposed inside the U-shaped cross-section mat.

10. The lead acid battery according to any one of claims 1 to 9, which is a valve-regulated lead acid battery.

Citation Information

Patent Citations

  • Sealed lead acid battery

    JP1998040896A

  • Separator for use in lead acid battery and lead acid battery using it

    JP2002313305A

  • Control valve type lead-acid battery

    JP2005327546A

  • Lead storage battery

    JP2014078325A

  • Lead storage battery

    JP2014207161A